The Effect of Graphene Oxide/Reduced Graphene Oxide Functionalized with Metal Nanoparticles on Dermal, Bacterial, and Cancerous/Non-Cancerous Epidermal Cells. Issue 22 (12th January 2016) - Isseroff, Rebecca; Chen, Arthur; Cho, Jae; Simon, Marcia; Jerome, Luckner J.; Rafailovich, Miriam
ABSTRACT: The unique planar structures and high surface area of graphene oxide (GO) and reduced graphene oxide (rGO) has induced great interest as drug delivery platforms. Silver and platinum nanoparticles are used in medicine, biotechnology and cosmetics and have electrocatalytic properties. However, GO has been found to be toxic to a variety of cells; pure graphene is insoluble; and nanoparticles aggregate, diminishing their activity. This research functionalized GO and rGO with silver or platinum nanoparticles (Ag/PtNPs) and experimental solutions were then tested on bacteria, dermal fibroblasts (DFBC's), and cancerous (SCC13's) and non-cancerous (DO33's) epidermal cells to determine toxicity and/or cell viability. GO was functionalized with Ag or Pt salts, forming metalized-GO; then reduced with NaBH4 . Ag-rGO, depending on nanoparticle size, killed either S. Aureus or K. Pneumoniae, while Pt-rGO and rGO had no effect . 1mM Ag-prGO concentrations diluted 1:100 with DMEM was toxic to SCC13 cancerous keratinocytes but showed reduced toxicity to DO33 non-cancerous keratinocytes; whereas Pt-rGO and rGO exerted little effect on SCC13's and DO33's at all concentrations. All test solutions adhered to DFBC's and influenced the orientation of their growth, suggesting potential use in wound dressings to aid healing.